In mathematics, the Christoffel–Darboux formula or Christoffel–Darboux theorem is an identity for a sequence of orthogonal polynomials , introduced by Elwin Bruno Christoffel (1858 ) and Jean Gaston Darboux (1878 ).
Christoffel–Darboux formula — if a sequence of polynomials
f
0
,
f
1
,
…
{\displaystyle f_{0},f_{1},\dots }
are of degrees
0
,
1
,
…
{\displaystyle 0,1,\dots }
, and orthogonal with respect to a probability measure
μ
{\displaystyle \mu }
, then
∑
j
=
0
n
f
j
(
x
)
f
j
(
y
)
h
j
=
k
n
h
n
k
n
+
1
f
n
(
y
)
f
n
+
1
(
x
)
−
f
n
+
1
(
y
)
f
n
(
x
)
x
−
y
{\displaystyle \sum _{j=0}^{n}{\frac {f_{j}(x)f_{j}(y)}{h_{j}}}={\frac {k_{n}}{h_{n}k_{n+1}}}{\frac {f_{n}(y)f_{n+1}(x)-f_{n+1}(y)f_{n}(x)}{x-y}}}
where
h
j
=
‖
f
j
‖
μ
2
{\displaystyle h_{j}=\|f_{j}\|_{\mu }^{2}}
are the squared norms, and
k
j
{\displaystyle k_{j}}
are the leading coefficients.
There is also a "confluent form" of this identity by taking
y
→
x
{\displaystyle y\to x}
limit:
Christoffel–Darboux formula, confluent form —
∑
j
=
0
n
f
j
2
(
x
)
h
j
=
k
n
h
n
k
n
+
1
[
f
n
+
1
′
(
x
)
f
n
(
x
)
−
f
n
′
(
x
)
f
n
+
1
(
x
)
]
.
{\displaystyle \sum _{j=0}^{n}{\frac {f_{j}^{2}(x)}{h_{j}}}={\frac {k_{n}}{h_{n}k_{n+1}}}\left[f_{n+1}'(x)f_{n}(x)-f_{n}'(x)f_{n+1}(x)\right].}
Lemma — Let
p
n
{\displaystyle p_{n}}
be a sequence of polynomials orthonormal with respect to a probability measure
μ
{\displaystyle \mu }
, such that
p
n
{\displaystyle p_{n}}
has degree
n
{\displaystyle n}
, and define
a
n
=
⟨
x
p
n
,
p
n
+
1
⟩
,
b
n
=
⟨
x
p
n
,
p
n
⟩
,
n
≥
0
{\displaystyle a_{n}=\langle xp_{n},p_{n+1}\rangle ,\qquad b_{n}=\langle xp_{n},p_{n}\rangle ,\qquad n\geq 0}
(they are called the "Jacobi parameters"), then we have the three-term recurrence[ 1]
p
0
(
x
)
=
1
,
p
1
(
x
)
=
x
−
b
0
a
0
,
x
p
n
(
x
)
=
a
n
p
n
+
1
(
x
)
+
b
n
p
n
(
x
)
+
a
n
−
1
p
n
−
1
(
x
)
,
n
≥
1
{\displaystyle {\begin{array}{l l}{p_{0}(x)=1,\qquad p_{1}(x)={\frac {x-b_{0}}{a_{0}}},}\\{xp_{n}(x)=a_{n}p_{n+1}(x)+b_{n}p_{n}(x)+a_{n-1}p_{n-1}(x),\qquad n\geq 1}\end{array}}}
Proof
By definition,
⟨
x
p
n
,
p
k
⟩
=
⟨
p
n
,
x
p
k
⟩
{\displaystyle \langle xp_{n},p_{k}\rangle =\langle p_{n},xp_{k}\rangle }
, so if
k
≤
n
−
2
{\displaystyle k\leq n-2}
, then
x
p
k
{\displaystyle xp_{k}}
is a linear combination of
p
0
,
.
.
.
,
p
n
−
1
{\displaystyle p_{0},...,p_{n-1}}
, and thus
⟨
x
p
n
,
p
k
⟩
=
0
{\displaystyle \langle xp_{n},p_{k}\rangle =0}
. So, to construct
p
n
+
1
{\displaystyle p_{n+1}}
, it suffices to perform Gram-Schmidt process on
x
p
n
{\displaystyle xp_{n}}
using
p
n
+
1
,
p
n
,
p
n
−
1
{\displaystyle p_{n+1},p_{n},p_{n-1}}
, which yields the desired recurrence.
Proof of Christoffel–Darboux formula
For any sequence of nonzero constants
c
0
,
c
1
,
…
{\displaystyle c_{0},c_{1},\dots }
, we can change each
f
k
{\displaystyle f_{k}}
to
c
k
f
k
{\displaystyle c_{k}f_{k}}
, and both sides of the equation would remain unchanged. Thus WLOG, scale each
f
n
{\displaystyle f_{n}}
to
p
n
{\displaystyle p_{n}}
.
Since
k
n
+
1
k
n
x
p
n
−
p
n
+
1
{\displaystyle {\frac {k_{n+1}}{k_{n}}}xp_{n}-p_{n+1}}
is a degree
n
{\displaystyle n}
polynomial, it is perpendicular to
p
n
+
1
{\displaystyle p_{n+1}}
, and so
⟨
k
n
+
1
k
n
x
p
n
,
p
n
+
1
⟩
=
⟨
p
n
+
1
,
p
n
+
1
⟩
=
1
{\displaystyle \langle {\frac {k_{n+1}}{k_{n}}}xp_{n},p_{n+1}\rangle =\langle p_{n+1},p_{n+1}\rangle =1}
. Thus,
a
n
=
k
n
k
n
+
1
{\textstyle a_{n}={\frac {k_{n}}{k_{n+1}}}}
.
Base case:
k
0
k
1
p
0
(
y
)
p
1
(
x
)
−
p
1
(
y
)
p
0
(
x
)
x
−
y
=
k
0
k
1
p
0
(
y
)
x
−
b
0
a
0
−
p
0
(
x
)
y
−
b
0
a
0
x
−
y
=
1
{\displaystyle {\frac {k_{0}}{k_{1}}}{\frac {p_{0}(y)p_{1}(x)-p_{1}(y)p_{0}(x)}{x-y}}={\frac {k_{0}}{k_{1}}}{\frac {p_{0}(y){\frac {x-b_{0}}{a_{0}}}-p_{0}(x){\frac {y-b_{0}}{a_{0}}}}{x-y}}=1}
Induction:
(
x
−
y
)
∑
j
=
0
n
p
j
(
x
)
p
j
(
y
)
=
(
x
−
y
)
∑
j
=
0
n
−
1
p
j
(
x
)
p
j
(
y
)
+
p
n
(
x
)
p
n
(
y
)
(
x
−
y
)
=
(IH)
k
n
−
1
k
n
[
p
n
(
x
)
p
n
−
1
(
y
)
−
p
n
(
y
)
p
n
−
1
(
x
)
]
+
(
x
−
y
)
p
n
(
x
)
p
n
(
y
)
{\displaystyle {\begin{aligned}&(x-y)\sum _{j=0}^{n}p_{j}(x)p_{j}(y)=(x-y)\sum _{j=0}^{n-1}p_{j}(x)p_{j}(y)+p_{n}(x)p_{n}(y)(x-y)\\&{\stackrel {\text{ (IH) }}{=}}{\frac {k_{n-1}}{k_{n}}}\left[p_{n}(x)p_{n-1}(y)-p_{n}(y)p_{n-1}(x)\right]+(x-y)p_{n}(x)p_{n}(y)\end{aligned}}}
By the three-term recurrence,
x
p
n
(
x
)
=
a
n
p
n
+
1
(
x
)
+
b
n
p
n
(
x
)
+
a
n
−
1
p
n
−
1
(
x
)
y
p
n
(
y
)
=
a
n
p
n
+
1
(
y
)
+
b
n
p
n
(
y
)
+
a
n
−
1
p
n
−
1
(
y
)
{\displaystyle {\begin{aligned}&xp_{n}(x)=a_{n}p_{n+1}(x)+b_{n}p_{n}(x)+a_{n-1}p_{n-1}(x)\\&yp_{n}(y)=a_{n}p_{n+1}(y)+b_{n}p_{n}(y)+a_{n-1}p_{n-1}(y)\end{aligned}}}
Multiply the first by
p
n
(
y
)
{\textstyle p_{n}(y)}
and the second by
p
n
(
x
)
{\textstyle p_{n}(x)}
and subtract:
(
x
−
y
)
p
n
(
x
)
p
n
(
y
)
=
a
n
[
p
n
(
y
)
p
n
+
1
(
x
)
−
p
n
(
x
)
p
n
+
1
(
y
)
]
+
a
n
−
1
[
p
n
(
y
)
p
n
−
1
(
x
)
−
p
n
(
x
)
p
n
−
1
(
y
)
]
{\displaystyle (x-y)p_{n}(x)p_{n}(y)=a_{n}\left[p_{n}(y)p_{n+1}(x)-p_{n}(x)p_{n+1}(y)\right]+a_{n-1}\left[p_{n}(y)p_{n-1}(x)-p_{n}(x)p_{n-1}(y)\right]}
Now substitute in
a
n
=
k
n
k
n
+
1
,
a
n
−
1
=
k
n
−
1
k
n
{\textstyle a_{n}={\frac {k_{n}}{k_{n+1}}},\quad a_{n-1}={\frac {k_{n-1}}{k_{n}}}}
and simplify.
The Hermite polynomials are orthogonal with respect to the gaussian distribution.
The
H
{\displaystyle H}
polynomials are orthogonal with respect to
1
π
e
−
x
2
{\displaystyle {\frac {1}{\sqrt {\pi }}}e^{-x^{2}}}
, and with
k
n
=
2
n
{\displaystyle k_{n}=2^{n}}
.
∑
k
=
0
n
H
k
(
x
)
H
k
(
y
)
k
!
2
k
=
1
n
!
2
n
+
1
H
n
(
y
)
H
n
+
1
(
x
)
−
H
n
(
x
)
H
n
+
1
(
y
)
x
−
y
.
{\displaystyle \sum _{k=0}^{n}{\frac {H_{k}(x)H_{k}(y)}{k!2^{k}}}={\frac {1}{n!2^{n+1}}}\,{\frac {H_{n}(y)H_{n+1}(x)-H_{n}(x)H_{n+1}(y)}{x-y}}.}
The
H
e
{\displaystyle He}
polynomials are orthogonal with respect to
1
2
π
e
−
1
2
x
2
{\displaystyle {\frac {1}{\sqrt {2\pi }}}e^{-{\frac {1}{2}}x^{2}}}
, and with
k
n
=
1
{\displaystyle k_{n}=1}
.
∑
k
=
0
n
H
e
k
(
x
)
H
e
k
(
y
)
k
!
=
1
n
!
H
e
n
(
y
)
H
e
n
+
1
(
x
)
−
H
e
n
(
x
)
H
e
n
+
1
(
y
)
x
−
y
.
{\displaystyle \sum _{k=0}^{n}{\frac {He_{k}(x)He_{k}(y)}{k!}}={\frac {1}{n!}}\,{\frac {He_{n}(y)He_{n+1}(x)-He_{n}(x)He_{n+1}(y)}{x-y}}.}
Associated Legendre polynomials :
(
μ
−
μ
′
)
∑
l
=
m
L
(
2
l
+
1
)
(
l
−
m
)
!
(
l
+
m
)
!
P
l
m
(
μ
)
P
l
m
(
μ
′
)
=
(
L
−
m
+
1
)
!
(
L
+
m
)
!
[
P
L
+
1
m
(
μ
)
P
L
m
(
μ
′
)
−
P
L
m
(
μ
)
P
L
+
1
m
(
μ
′
)
]
.
{\displaystyle {\begin{aligned}(\mu -\mu ')\sum _{l=m}^{L}\,(2l+1){\frac {(l-m)!}{(l+m)!}}\,P_{lm}(\mu )P_{lm}(\mu ')=\qquad \qquad \qquad \qquad \qquad \\{\frac {(L-m+1)!}{(L+m)!}}{\big [}P_{L+1\,m}(\mu )P_{Lm}(\mu ')-P_{Lm}(\mu )P_{L+1\,m}(\mu '){\big ]}.\end{aligned}}}
Christoffel–Darboux kernel[ edit ]
The summation involved in the Christoffel–Darboux formula is invariant by scaling the polynomials with nonzero constants. Thus, each probability distribution
μ
{\displaystyle \mu }
defines a series of functions
K
n
(
x
,
y
)
:=
∑
j
=
0
n
f
j
(
x
)
f
j
(
y
)
/
h
j
,
n
=
0
,
1
,
…
{\displaystyle K_{n}(x,y):=\sum _{j=0}^{n}f_{j}(x)f_{j}(y)/h_{j},\quad n=0,1,\dots }
which are called the Christoffel–Darboux kernels . By the orthogonality, the kernel satisfies
∫
f
(
y
)
K
n
(
x
,
y
)
d
μ
(
y
)
=
{
f
(
x
)
,
f
∈
Span
(
p
0
,
p
1
,
…
,
p
n
)
0
,
∫
a
b
f
(
x
)
p
ℓ
(
x
)
d
μ
(
x
)
=
0
(
ℓ
=
0
,
1
,
…
,
n
)
{\displaystyle \int f(y)K_{n}(x,y)\mathrm {d} \mu (y)={\begin{cases}f(x),&f\in \operatorname {Span} \left(p_{0},p_{1},\ldots ,p_{n}\right)\\0,&\int _{a}^{b}f(x)p_{\ell }(x)\mathrm {d} \mu (x)=0(\ell =0,1,\ldots ,n)\end{cases}}}
In other words, the kernel is an integral operator that orthogonally projects each polynomial to the space of polynomials of degree up to
n
{\displaystyle n}
.
Andrews, George E.; Askey, Richard; Roy, Ranjan (1999), Special functions , Encyclopedia of Mathematics and its Applications, vol. 71, Cambridge University Press , ISBN 978-0-521-62321-6 , MR 1688958
Christoffel, E. B. (1858), "Über die Gaußische Quadratur und eine Verallgemeinerung derselben." , Journal für die Reine und Angewandte Mathematik (in German), 55 : 61– 82, doi :10.1515/crll.1858.55.61 , ISSN 0075-4102 , S2CID 123118038
Darboux, Gaston (1878), "Mémoire sur l'approximation des fonctions de très-grands nombres, et sur une classe étendue de développements en série", Journal de Mathématiques Pures et Appliquées (in French), 4 : 5– 56, 377– 416, JFM 10.0279.01
Abramowitz, Milton; Stegun, Irene A. (1972), Handbook of Mathematical Functions , Dover Publications, Inc., New York , p. 785, Eq. 22.12.1
Olver, Frank W. J.; Lozier, Daniel W.; Boisvert, Ronald F.; Clark, Charles W. (2010), "NIST Handbook of Mathematical Functions" , NIST Digital Library of Mathematical Functions , Cambridge University Press , p. 438, Eqs. 18.2.12 and 18.2.13, ISBN 978-0-521-19225-5 (Hardback, ISBN 978-0-521-14063-8 Paperback)
Simons, Frederik J.; Dahlen, F. A.; Wieczorek, Mark A. (2006), "Spatiospectral concentration on a sphere", SIAM Review , 48 (1): 504– 536, arXiv :math/0408424 , Bibcode :2006SIAMR..48..504S , doi :10.1137/S0036144504445765 , S2CID 27519592